A brief review on Word Sense Disambiguation Approaches - Kale, Swati; Gawande, Ujjwala (International Journal of Engineering and Technology, 2018)
To deal with the problem of text retrieval, machine translation, query processing, speech processing, the word sense disambiguation (WSD) performs very important role. WSD is an AI complete problem. This paper presents the significance, approaches along withÂ work done in the field ofÂ WSD. Â Apple amount of work has been done in WSD forÂ foreign languages but for Indian languages this issue is still about to concern. This paper tries to find out different limitations and challenges in WSD, based on which better approach will beÂ decided by the researchers to solve the problem of WSD.